Manufactured Sand as River Sand Replacement for Masonry Binding Mortar - Kosalya, S.; Arvinthan, P.; Sathiparan, N. (IEEE, 2021)
Binding mortar establish as an essential part of masonry for binding the masonry units together. Natural sand or river sand is used as a fine aggregate with cement for masonry binding mortar. Although the demand for river sand increases rapidly, on another side, the supply of good quality river sand is reduced due to restrictions in river sand mining. Therefore, there is increasing interest in finding alternative materials for river sand. Manufactured sand is one of the alternatives as it has some advantages over river sand. It provides a better contribution to the strength of the cementitious material, better workability, lesser cement consumption, and eco-friendly. The present study is focused on the progress of a sustainable masonry binding mortar by experimental investigations with manufactured sand as a replacement for river sand. Test for compressive strength was conducted on brick, binding mortar with various combinations of river sand and manufactured sand and masonry prism with different binding mortar. Test results showed that manufactured sand incorporated binding mortar not only shows better compressive strength itself but also significantly improved the compressive strength of masonry.
Keywords: Masonry; Compressive strength; River sand; Manufactured sand